Pelatihan Ecoprint Sebagai Pemberdayaan Ekonomi Kreatif Bagi Ibu- Ibu PKK Desa Padelegan Pamekasan - Rahmawati, Ika Dian; A’yun, Dya Qurotul; Ningsih, Puji Rahayu; Nikmah, Ainun; A’la, Rosyidatul; Nifa, Maulidia; Musdhalifa, Lifnon Falahus Puja Putri; Aprilianyani, Riswanda Rurye (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This service aims to increase the knowledge and skills of partners in making ecoprints. Research methodology: (1) the first step in ecoprint making training is the scouring, mordanting, and blanket coloring stages; (2) the practice of making ecoprints using the pounding and steam method for PKK women was given using demonstration and training methods, (3) training on packaging ecoprint products, and (4) training on marketing ecoprints  (atik products by creating a promotional website. Results: The methods implemented in this community service are: (1) the first step in t; (ining for making ecoprints is the scouring;, mordanting and blanket coloring stages; 2) the practice of making Ecoprint using the pounding and steam method for PKK women was given using demonstration and training methods, 3) training on packaging ecoprint products and (4) training on marketing ecoprint batik products by creating a promotional website. Conclusions: The ecoprint training enhanced the skills and creativity of PKK women in Padelegan Village by teaching them to use natural materials to create eco-friendly fabric designs. This activity promotes innovation, raises environmental awareness, and opens up new economic opportunities. Limitations: Business opportunities for Padelegan village residents can be realized, residents' incomes can increase, and innovative ideas for new businesses can emerge among Padelegan village residents. Contribution: The activities are carried out using the knowledge transfer method in the form of sharing knowledge regarding packaging design, which is included in the scientific realm of visual communication design, especially in the field of advertising.